Manajemen Kegiatan Ekstrakurikuler Dalam Meningkatkan Prestasi Non Akademik Siswa - Ayu Sundari (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2021)
Extracurricular activities are a place for students who have interests and talents. Extracurricular activities can help develop self-potential in increasing student achievement. Student achievement is not only obtained from academic achievement, with non-academic achievements students can be able to communicate and socialize well. Good extracurricular management will result in achievements in non-academic fields. Madrasah Aliyah Negeri 1 Mojokerto is one of the madrasas that has produced many students with non-academic achievements. The results of this study are (1) the management of extracurricular activities at Madrasah Aliyah Negeri 1 Mojokerto includes, first planning for extracurricular activities carried out at the beginning of the new academic year, secondly organizing is carried out by extracurricular guidance teachers by assigning assignments to coaches who have competence in their fields. The third implementation of extracurricular activities is carried out every day according to a predetermined schedule, the fourth supervision is carried out with the presence of the supervisor and students. (2) students' non-academic achievement after the management of extracurricular activities is good and is increasing. Judging from the educational process that went well and smoothly, the existence of good extracurricular management at Madrasah Aliyah Negeri 1 Mojokerto was able to achieve achievements, both at the district and provincial levels.